73 Early effects of transcatheter aortic valve implantation (TAVI) on left ventricular remodelling and longitudinal function: an echocardiographic study. (June 2018) - Badiani, Sveeta; Zalen, Jet van; Ramasamy, Anantharaman; Ozkor, Mick; Mathur, Anthony; Kennon, Simon; Mullen, Michael; Bhattacharyya, Sanjeev; Lloyd, Guy
Abstract : Background: The left ventricular response to aortic stenosis is complex. Transcatheter aortic valve implantation (TAVI) decreases the left ventricular afterload by reducing the transvalvular pressure gradient; however data is limited regarding its immediate impact on left ventricular geometry, function and remodelling. Purpose: This study sought to assess left ventricular remodelling and longitudinal function immediately following TAVI. Methods: Data from 368 patients with severe aortic stenosis undergoing TAVI at our institution was retrospectively analysed. Patients without both an in-house pre and post procedure echocardiogram available for analysis were excluded, as were patients with suboptimal echocardiographic windows. The post TAVI echocardiogram was performed at 1.4±1 days. Results: 222 patients were included in the final analysis. 119 patients (53.6%) were female and the mean age was 82.6±7.4 years. Aortic valve area was 0.7±0.3 cm 2 before TAVI and increased to 2.1±1.8 cm 2 after intervention. Mean transvalvular gradient decreased from 46±16 mmHg to 10±5 mmHg. There were no significant changes in left and right ventricular dimensions, left ventricular volume, left ventricular ejection fraction (LVEF) and right ventricular function immediately following TAVI. Left ventricular longitudinal function measured using S prime improved significantly post TAVI ((5±2 to 6±2 (medial) and 6±2 to 7±2 (lateral), p=0.001). Although relative wall thickness and left ventricular mass decreased post intervention, these changes were not significant (RWT 0.54±0.19 vs 0.52±0.16; p=0.32, LV mass 207±67 vs 196±58; p=0.098). A subgroup analysis of relative wall thickness and left ventricular mass in patients was performed. with patients classified into high gradient AS with normal ejection fraction (HGNEF), high gradient AS with reduced EF (HGREF), low gradient AS with normal EF (LGNEF) and low gradient AS with reduced EF (LGREF), which yielded similar results to the above. HGNEF (n=133): Pre TAVI RWT 0.56±0.20 vs Post TAVI RWT 0.54±0.15, Pre TAVI LV mass 200±65 vs 190±61, HGREF (n=37): 0.51±0.21 vs 0.52±0.20, p=0.441, LV mass 218±63, 218±63, p=0.777 LGNEF (n=31): 0.54±0.20 vs 0.50±0.13, p=0.322, 175±53, 172±53, p=0.681 LGREF (n=31): 0.44±0.13 vs 0.44±0.15, p=0.680, 232±79, 207±59, p=0.236 The patients with low gradient and reduced ejection fraction did not show significant improvements in medial S' as compared with the other groups (S' 4.5±1.6 pre TAVI vs 4.9±1.9 post TAVI, p=0.320) Conclusions: Our data demonstrates a significant improvement in left ventricular longitudinal myocardial function immediately following TAVI, despite no change in conventional measures of left ventricular function. There were no significant effects on relative wall thickness and left ventricular mass; however the medium and long term effects are yet to be defined.